USING BENCHMARKING TO REDUCE THE FABRICATION COST – A TECHNOLOGICAL ANALYSIS FOR A PART - Catalina Enache; Florina Chischop; Narcisa Valter; Mioara Duca (Journal of Industrial Design and Engineering Graphics, 2019)
Benchmarking is an approach that involves confronting your organization's own practices with those of other organizations. The benchmarking term involves the measurement that can be obtained by comparing internal and external practices and the result of significant differences can be analyzed and taken into account. This type of approach can lead to higher chances of success because it requires a good understanding of the quality of the products in the competing groups and are being analyzed the competitor’s strategies for development, production, supply and financial. In this article we will analyze the technological flow of obtaining a part, which we will call "plastic niche reinforcement", for which the realization costs will be identified. The objective is to see if the cost of achieving this part falls within the proposed target and if not what decisions can be taken from a constructive point of view to reduce costs.